Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep32649
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-glucosidase inhibitors and hepatotoxicity in type 2 diabetes: a systematic review and meta-analysis

Abstract: Alpha-glucosidase inhibitors (AGIs) was reported to be associated with several rare adverse hepatic events, but with inconsistent results. We aimed to investigate the risk of hepatotoxicity associated with the use of AGIs in patients with type 2 diabetes mellitus (T2DM), and performed a systematic review and meta-analysis. Fourteen studies (n = 2881) were eligible, all of which were RCTs. Meta-analysis of data regarding elevation of more than 3-fold the upper limit of normal (ULN) of AST and ALT showed statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 54 publications
1
29
0
1
Order By: Relevance
“…The high‐TB instant dark tea from the present study had an inhibition rate of 81.8%, which was the highest α ‐glucosidase inhibitory activity among all of the tested instant dark tea samples. α ‐Glucosidase inhibitors could hinder the rapid absorption of carbohydrates by the body, comprising a postprandial hyperglycemia treatment . He et al reported that different molecular levels of TB (≤3.5, 3.5–25, 25–50, 50–100 and ≥ 100 kDa) had an effect on hypoglycemia, particularly 25–50 kDa TB, which was 1.9 times as active as acarbose.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The high‐TB instant dark tea from the present study had an inhibition rate of 81.8%, which was the highest α ‐glucosidase inhibitory activity among all of the tested instant dark tea samples. α ‐Glucosidase inhibitors could hinder the rapid absorption of carbohydrates by the body, comprising a postprandial hyperglycemia treatment . He et al reported that different molecular levels of TB (≤3.5, 3.5–25, 25–50, 50–100 and ≥ 100 kDa) had an effect on hypoglycemia, particularly 25–50 kDa TB, which was 1.9 times as active as acarbose.…”
Section: Resultsmentioning
confidence: 98%
“…-Glucosidase inhibitors could hinder the rapid absorption of carbohydrates by the body, comprising a postprandial hyperglycemia treatment. 30,31 He et al 32 reported that different molecular levels of TB (≤3.5, 3.5-25, 25-50, 50-100 and ≥ 100 kDa) had an effect on hypoglycemia, particularly 25-50 kDa TB, which was 1.9 times as active as acarbose. In addition, tea polysaccharides, 33 tea polyphenols 34 and theaflavins 35 had an inhibitory effect on -glucosidase activity.…”
Section: -Glucosidase and Pancreatic Lipase Inhibitory Activitiesmentioning
confidence: 99%
“…Currently, numerous synthetic AGIs, such as acarbose, miglitol, and voglibose, are exactly efficient in attenuating the rise of blood glucose levels. However, side effects including liver toxicity and adverse gastrointestinal symptoms have seriously limited their application in clinical treatment (Zhang, Chen et al, ). Thus, AGIs, which have no adverse or unwanted secondary effects, are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient α‐glucosidase inhibitors (AGIs) is currently taken as a promising proposal to suppress blood glucose level, which then prevents diabetes and diabetic complications (Ali, Houghton, & Soumyanath, ; Tiwari, Kumbhare, Agawane, Ali, & Kumar, ). However, acarbose, a synthetic AGIs, exhibits toxic side effects such as angina abdominis, bloating, diarrhea, and even hepatotoxicity (Zhang, Chen, et al, ). At present, many studies have proved that plant extracts possess the potential to be a better source of AGIs, which takes the advantages of natural, high‐efficiency, inexpensive, and low toxicity.…”
Section: Introductionmentioning
confidence: 99%